PECULIARITIES OF THE CONSTRUCTION OF A PEDAGOGICAL EXPERIMENT IN THE FIELD OF PHYSICAL CULTURE AND SPORTS (Physical Culture and Sport: Scientific Perspective, 2023)
The article deals with the analysis of peculiarities of the construction and realization of a pedagogical experiment in the field of physical culture and sports. Only those phenomena that can be reproduced repeatedly under experimental conditions can be considered as scientific ones. Pedagogical experiment creates such an opportunity to reproduce the studied phenomena. Organization of specially created conditions involves systemic changes over a long period with the parallel establishment of regularities of the studied phenomenon. To obtain the objective results from realization of pedagogical experiment is possible only if the accompanying factors that cause side factors are carefully controlled. The side factors can «distort» the results of a pedagogical experiment, so they should be eliminated in order to create evidence of the effect of the experimental factor. Any experimental factor in the process of comparative analysis with a traditional one must have a disparity. The concept of disparity is conditioned by an obligatory requirement: the factors that are matched must be directed to performing the same task. Evidence of the research with the experimental task can be reached under the condition of simultaneous study of the relations of this sports and pedagogical factor with the entire system.Duration of pedagogical experiment is determined in each specific case individually. It depends on the research tasks and the complexity of their solution. Studying the influence of means of physical education or sport training on the development of human mental sphere, is ought to understand that the experiment should last at least one year. An analogical situation is with the process of educating personal human qualities. Pedagogical studies usually also last one or two years.  Experiment with the participation of schoolchildren or students must take into account the structure and calendar terms of the academic year.
Keywords: pedagogical experiment; physical culture; sports; disparity; factors; evidence